2017
DOI: 10.5539/jas.v10n1p325
|View full text |Cite
|
Sign up to set email alerts
|

Soil Chemistry and Cucumber (Cucumis sativus L.) Yield as Influenced by 16 Years of Composted Poultry Litter Addition

Abstract: Poultry litter is increasingly used as organic amendment in market gardening in Côte d'Ivoire. To know about the sustainability of this practice, its impacts on soil quality should be known. This study aimed at assessing the effect on soil fertility of composted poultry litter addition for 16 years following two distinct ways, and identifying soil parameters driving cucumber yield. Trials were laid out in a Fisher randomized block design with 3 treatments replicated 5 times each: Control (C), Surface-applied c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Indeed, data of the present study showed that low soil pH led to limited lateral root development. In addition such soil condition is known to reduce the availability of nutrients, particularly exchangeable cations that are determinant in cucumber growth and fruit production as recently reported by Abobi et al (2018). Note.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, data of the present study showed that low soil pH led to limited lateral root development. In addition such soil condition is known to reduce the availability of nutrients, particularly exchangeable cations that are determinant in cucumber growth and fruit production as recently reported by Abobi et al (2018). Note.…”
Section: Discussionmentioning
confidence: 93%